Evaluation of surface roughness of rock-like joints using close range photogrammetry method. Issue 1 (1st January 2023) - Momeni, A; Torkan, M; Azhari, A; Uotinen, L; Baghbanan, A
Abstract: The surface roughness of the joints affects their hydraulic and mechanical behavior. There are various methods for assessing the surface roughness of discontinuities. With the development of photography technology and the release of powerful software, a photogrammetric analyzer has been introduced as a non-contact surface evaluation method. In this research, a three-dimensional model of the fracture surface was constructed using the close-range photogrammetric procedure and the joint roughness coefficient (JRC) is derived from the surface profiles. Also, the surface profiles were surveyed using the Profilometers (Barton Comb) and the JRC values were obtained using the Z2 method. Calculations were performed in two sampling steps of 0.42 and 1.27 mm. Ultimately, the results of the two methods were compared. A Sony Cybershot HX1 digital camera was used to capture the images. To process the images and build the 3D model, they were loaded in the "Agisoft metashape" software. A point cloud data was obtained with very high accuracy with a distance of 0.13 mm between points in the 3D model. The results show that the JRC values obtained from the photogrammetry method, for the upper surface of the joint, recorded 8% and 11% difference from the joint surface for sampling intervals of 1.27 and 0.42 mm, respectively. While for the bottom surface of the joint, these differences were 6.1% and 10% for sampling intervals of 1.27 and 0.42 mm, respectively.